Preparation and Evaluation of Acetabularia-Modified Carbon Paste Electrode in Anodic Stripping Voltammetry of Copper and Lead Ions - Muhammad Raziq Rahimi Kooh; Jose H. Santos; Muhammad Khairud Dahri (Journal of Chemistry)
Seaweed is well known about for potential in chelating heavy metals. In this study, carbon paste electrodes were fabricated with siphonous seaweed Acetabularia acetabulum as the modifiers to sense lead (II) and copper (II) by square-wave anodic stripping voltammetry. Various scan rates and deposition potentials were measured to obtain the optimal peak current for Pb(II) and Cu(II). Optimum conditions of Acetabularia-CPE for sensing Pb(II) were at the scan rate of 75 mV/s and deposition potential of −800 mV, while for Cu(II) sensing were at 100 mV/s and −300 mV, respectively. The electrodes were characterized by the duration of accumulation time, preconcentration over a range of standards, supporting electrolyte, and standard solutions of various pH values. Interference studies were carried out. Both Zn(II) and Cu(II) were found to interfere with Pb(II) sensing, whereas only Zn(II) causes interference with Cu(II) sensing. The electrode was found to have good regeneration ability via electrochemical cleaning. Preliminary testing of complex samples such as NPK fertilisers, black soil, and sea salt samples was included.